Reviving Tradition: The Modern Evolution of the Gurukul Education System - Adhikari, Toya Nath (Creative Vision: Multidisciplinary Journal of PMC, 2025)
This research article explores the evolution of the Gurukul education system, examining its historical roots, core principles, and modern developments. The study analyzes how cultural, religious, and traditional factors, as well as global trends, have shaped the Gurukul system, highlighting its unique features and contributions to education. The article also investigates the challenges and opportunities facing the Gurukul system in today’s rapidly changing world, emphasizing its importance in promoting holistic development and global citizenship. Through a qualitative research approach, the study demonstrates that the Gurukul system embodies an integrated learning approach, prioritizing academic excellence, and social, spiritual, moral, and physical well-being. By fostering a strong teacher-student bond and focusing on comprehensive student development, the Gurukul system lays the foundation for lifelong learning and personal growth. By merging traditional and modern perspectives, educators can extract valuable lessons for contemporary education frameworks, aiming to promote well-rounded development. The article’s findings show that the Gurukul system has achieved significant academic success in today’s world to revive ancient knowledge systems.